Survey Data on Attitudes Towards Foreign Aid & Development in France, Germany, Great Britain, and the U.S - Torres-Raposo, Felipe; Oh, Soomin; Morini, Paolo; Hudson, Jennifer; Hudson, David (Scientific data, 2025)
Public support is crucial for shaping effective foreign aid policy and development cooperation. The Development Engagement Lab (DEL) has conducted surveys in France, Germany, Great Britain, and the United States to track and analyse public attitudes towards foreign aid and engagement with sustainable development. This data descriptor presents multiple datasets, identifying shifts in public opinion and behaviours, alongside underlying mechanisms explaining these attitudes and actions. The dataset comprises nationally representative panel data (2019 - 2024), repeated cross-sections (2019 - 2024), and several foreign aid subject-specific datasets. The DEL data contains 91 unique datasets, with 270,829 observations from 130,286 unique respondents. We have developed an R package, DELdata , to facilitate the use and dissemination of these datasets. These data will enable scholars, practitioners, and policymakers to produce valuable insights that will generate a better understanding of how citizens think about, and engage with, foreign aid and sustainable development.